2020
DOI: 10.22541/au.160397366.64581136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Could LUTS be Early Symptoms of COVID-19

Abstract: Aim: To show if lower urinary tract symptoms (LUTS) could be symptoms of COVID-19 with validated questionnaires.Methods: The 96 COVID-19 patients who were hospitalized at a tertiary center were collected retrospectively. After the exclusion criteria, 46 patients were consisted as the study population. The male and female patients then fill formed the International Prostate Symptom Score and Urinary Symptom Profile respectively. All patients responded to these questions for the three period. Results: 27 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Urinary tract involvement was reported in five studies (Table 2). 26–29 In detail, de novo lower urinary tract symptoms (LUTS) and deterioration of pre‐existing LUTS occurred in 43 and 7 patients, respectively. Validated questionnaires to score LUTS were adopted in two studies 28,29 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Urinary tract involvement was reported in five studies (Table 2). 26–29 In detail, de novo lower urinary tract symptoms (LUTS) and deterioration of pre‐existing LUTS occurred in 43 and 7 patients, respectively. Validated questionnaires to score LUTS were adopted in two studies 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Further assessment of eligibility, based on full‐text papers, led to the exclusion of nine papers. Finally, 16 studies involving a total of 575 patients infected with SARS‐CoV‐2 who had been evaluated for urinary and/or male genital involvement between January and June 2020 were included in the final analysis 17–31 (Figure 1). The characteristics of selected studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these contradictory studies, the urinary frequency was reported as a common symptom of COVID‐19 in a recent study 8 . Furthermore, Kaya et al reported that LUTS might be one of the initial symptoms of COVID‐19 14 …”
Section: Discussionmentioning
confidence: 99%